The effect of antepartum depressive and anxiety symptoms on mother-infant interaction: the mediating role of antepartum maternal emotional stress - Wriedt-Monske, Sophia; Müller, Mitho; Reck, Corinna; Nonnenmacher, Nora; Zietlow, Anna-Lena; Woll-Weber, Christian F. J. (Infant behavior and development, 2024)
Anxiety disorders, depression, and emotional stress during the antepartum period are interlinked with adverse child development. The quality of the dyadic interaction seems to play a crucial role in the transmission of these effects. In this study, we explored the mediating effect of antepartum maternal emotional stress (assessed via the Prenatal Emotional Stress Index) regarding the relationship of antepartum maternal depressive (assessed via the Edinburgh Postpartum Depression Scale), anxiety symptoms (assessed via the Stat-Trait-Anxiety-Inventory), and depressive and anxiety disorders (assessed according to the DSM-IV-TR) in the antepartum period on postpartum interactive quality in a longitudinal design. The Face-to-Face-Still-Face Paradigm (FFSF) and the Infant and Caregiver Engagement Phases (ICEP-R) coding system were used to assess the postpartum interactive qualities of the mother-infant dyads. The sample consisted of 59 women, 38 in the clinical and 21 in the control group. We found significant indirect effects of antepartum depressive symptoms and maternal diagnostic status on the mother’s neutral engagement and on the latency to the first social positive interactive match during the interaction - effects that were mediated by antepartum stress. Moreover, there was an indirect effect of state anxiety on neutral engagement - mediated by antepartum stress. Therapeutic intervention studies focusing on maternal antepartum regulation of emotional stress and postpartum interactive patterns might be crucial to encounter maladaptive developmental trajectories.
Gesehen am 30.09.2024